Ethiopia Stretching Forth Her Hands Unto God (Africa’s Service to the World) - Blyden, Edward Wilmot (Christianity, Islam and the Negro race, 1967)
xviii, ix, 407 pages ; 23 cm; "This reissue ... is a reprint of the first edition of 1887 ... printers' errors in the original have been corrected and a new index has been provided."–Page xvii; Includes bibliographical references; Mohammedanism and the Negro race – Christianity and the Negro race – Christian missions in West Africa – The aims and methods of a liberal education for Africans – The origin and purpose of African colonization – Ethiopia stretching out her hands unto God (Africa's service to the world) – Echoes from Africa – Philip and the eunuch – Mohammedanism in Western Africa – Sierra Leone and Liberia – Islam and race distinctions – Africa and the Africans – Life of Lord Lawrence and its lessons – The Mohammedans of Nigritia – African colonization
free
Keywords: Christianity – Africa